2002
DOI: 10.1021/bi0120291
|View full text |Cite
|
Sign up to set email alerts
|

The (αF357C)3(βR372C)3γ Subcomplex of the F1-ATPase from the Thermophilic Bacillus PS3 Has Altered ATPase Activity after Cross-Linking α and β Subunits at Noncatalytic Site Interfaces

Abstract: In crystal structures of bovine MF(1), the side chains of alpha F(357) and beta R(372) are near the adenines of nucleotides bound to noncatalytic sites. To determine if during catalysis these side chains must pass through the different arrangements in which they are present in crystal structures, the catalytic properties of the (alpha F(357)C)(3)(beta R(372)C)(3)gamma subcomplex of the TF(1)-ATPase were characterized before and after cross-linking the introduced cysteines with CuCl(2). The unmodified mutant en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…On the basis of the catalytic characteristics of other mutant R 3 β 3 γ subcomplexes of TF 1 (23), this indicates that subcomplexes containing the βE 395 C substitution have a greater propensity to entrap inhibitory MgADP in a catalytic site during turnover. Previous studies have shown that nucleotide-depleted MF 1 (24) and the nucleotide-depleted wild-type R 3 β 3 γ subcomplex of TF 1 (14) hydrolyze 50 µM ATP in three distinct phases: an initial In an earlier study, we demonstrated that the ATPase activity of the oxidized (RF 357 C) 3 (βR 372 C) 3 γ double mutant containing R-β cross-links at two noncatalytic site interfaces was stimulated 13-fold by LDAO, whereas the ATPase activity of the non-cross-linked double mutant was stimulated 5.7-fold by the detergent (17). In crystal structures of bovine MF 1 , the 392 GMDELS 397 segment is the turn in the helixturn-helix motif in the C-terminal domain of β subunits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the basis of the catalytic characteristics of other mutant R 3 β 3 γ subcomplexes of TF 1 (23), this indicates that subcomplexes containing the βE 395 C substitution have a greater propensity to entrap inhibitory MgADP in a catalytic site during turnover. Previous studies have shown that nucleotide-depleted MF 1 (24) and the nucleotide-depleted wild-type R 3 β 3 γ subcomplex of TF 1 (14) hydrolyze 50 µM ATP in three distinct phases: an initial In an earlier study, we demonstrated that the ATPase activity of the oxidized (RF 357 C) 3 (βR 372 C) 3 γ double mutant containing R-β cross-links at two noncatalytic site interfaces was stimulated 13-fold by LDAO, whereas the ATPase activity of the non-cross-linked double mutant was stimulated 5.7-fold by the detergent (17). In crystal structures of bovine MF 1 , the 392 GMDELS 397 segment is the turn in the helixturn-helix motif in the C-terminal domain of β subunits.…”
Section: Discussionmentioning
confidence: 99%
“…Inactivation of five subunit TF 1 (R 3 β 3 γδ ) with 5′-p-fluorosulfonyl[ 3 H]adenosine is caused by derivatization of the equivalent of βY 368 in MF 1 (26). After cross-linking the introduced cysteines in the (RF 357 C) 3 (βR 372 C) 3 γ subcomplex of TF 1 , the ATPase activity was reduced to 10% of the rate catalyzed by the wild-type subcomplex (17). Therefore, it is reasonable to assume that substitution of βE 395 in the 392 GMDELS 397 segment with Cys or Ala might affect the orientation of the R subunit with respect to the β subunit at the noncatalytic site interface, thereby altering the affinity of noncatalytic sites for nucleotides or affecting the conformational equilibrium between noncatalytic and catalytic sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 280-nm excitation wavelength with a 5-nm bandpass and a 345-nm emission wavelength with a 10-nm bandpass were used for the measurements. Details of performing the measurements were described previously (Bandyopadhyay et al, 2002; Jurasekova et al, 2009).…”
Section: Methodsmentioning
confidence: 99%